Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The degree of availability of administrative excellence standards among school principals at Tafila Governorate from the teachers' perspectivesDr. Hani Ahmad Alkriameen2. The degree of employing blended learning from the perspectives of principals and teachers of Palestinian public schools in the Nablus districtDr. Sherine Adnan Hashaika, Prof. Afnan Nazeer Darwazeh3. Effectiveness of Animated Films on Language Development in Early Childhood from the Mothers' Point of ViewMrs. Ashwaq Alloush Saud Al-Dawish4. Differences in Visual Perception Skills between Reading Disabilities and Low Achievement Primary Student in the Kingdom of BahrainDr. Zainab A. Albannai5. The challenges faced by kindergarten teachers with distance education under the Corona pandemicMrs. Fatimah Ali Al-Harbi6. University Violence and its Relationship to Irrational Ideas and Methods of Family Upbringing Among a Sample of Palestinian University Students (Al-Quds Open University as a Model)Dr. Mai Hassan Atiya , Dr. Saeeda Muhammad Abu Shakra7. The Anxiety Caused by the COVID-19 Pandemic on a Sample of High School Students in Public Education in Jeddah after Returning Back to School: Case StudyMrs. Norah Dakhilallah Alsubaie, Mrs. Hafsa Saleh Almudhi, Dr. Alaa Ibrahim Kutbi8. The Influence of Irrational Thinking and Social Networks on Citizenship Values for Undergraduate Students in Sultanate of OmanDr. Moosa Sulieman Al- Shuaili
Keywords: Journal of Educational and Psychological Sciences